Harnessing computational immunology to design targeted subunit vaccines for infectious bursal disease in poultry - Oladipo, Elijah Kolawole; Adeyemo, Stephen Feranmi; Oshoneye, Ayomiposi Isaiah; Akintola, Hannah Blessing; Elegbede, Bolatito Islam; Ayoomoba, Tobiloba Uren; Atilade, Dorcas Ayomide; Adegboye, Omolara Omoboye; Ejikeme, Abuoma Elizabeth; Balogun, Chris Olamide; Aderibigbe, Kehinde Abolade; Popoola, Possible Okikiola; et al. (Frontiers in Bioinformatics, 2025)
IntroductionInfectious bursal disease (IBD), caused by the infectious bursal disease Q8 virus (IBDV), is a highly contagious disease in young chickens, leading to immunosuppression with great economic importance. IBDV, a non-enveloped virus with a bipartite dsRNA genome, infects the bursa of Fabricius, causing severe gastrointestinal disease. Effective vaccines are urgently needed due to the limitations of current oral vaccines, including gastrointestinal degradation and low immunogenicity. This study designs and evaluates a multiepitope subunit vaccine using immunoinformatics.MethodsSequences of the IBDV structural proteins VP2 and VP3 were obtained from the National Centre for Biotechnology Information) NCBI. These are structural proteins VP2 and VP3 were subjected to the Vaxijen 2.0 webserver to predict the antigenicity, ToxiPred to predict the toxicity and further analyzed to identify immunogenic epitopes of Chicken Leukocyte Antigens (CLAs) using the NetMHCpan 4.1 webserver.ResultsThe final vaccine construct includes 2 HTL, 21 CTL, and 7 LBL epitopes, with gallinacin-3 precursor as an adjuvant. The construct is antigenic (0.5605), non-allergenic, and non-toxic, consisting of 494 amino acids with a molecular weight of 54.88 kDa and a positive charge (pI of 9.23). It is stable, hydrophilic, and soluble. Population coverage analysis revealed a global immune coverage of 89.83%, with the highest in Europe (99.86%) and the lowest in Central America (25.01%). Molecular docking revealed strong interactions with TLR-2_1, TLR-4, and TLR-7, with TLR-7 exhibiting the highest binding affinity (−366.15 kcal/mol). Immune simulations indicated a robust immune response, with high initial IgM levels, sustained IgG, memory cell formation, and activation of T helper (Th) cells 1 and 2, Natural Killer (NK) cells, and dendritic cells, suggesting potential long-lasting immunity against IBDV.DiscussionThis study presents a promising multi-epitope subunit vaccine candidate capable of effective immunization against IBDV with broad population coverage. However, further in vivo experimental validation is required to confirm its efficacy and safety.